Omega-6: Omega-3 PUFA Ratio, Pain, Functioning, and Distress in Adults With Knee Pain. Issue 2 (February 2018) - Sibille, Kimberly T.; King, Christopher; Garrett, Timothy J.; Glover, Toni L.; Zhang, Hang; Chen, Huaihou; Reddy, Divya; Goodin, Burel R.; Sotolongo, Adriana; Petrov, Megan E.; Cruz-Almeida, Yenisel; Herbert, Matthew; et al.
Abstract : Objectives: Osteoarthritis (OA) is associated with inflammation, chronic pain, functional limitations, and psychosocial distress. High omega-3 ( n- 3) polyunsaturated fatty acids (PUFAs) are associated with lower levels of inflammatory mediators, anti-nociception, and adaptive cognitive/emotional functioning. High omega-6 ( n -6) PUFAs are associated with inflammation, nociception, and psychological distress. While findings related to n -3 supplementation in knee OA are mixed, consideration of the n -6: n -3 ratio and additional outcome measures may provide improved understanding of the potential relevance of these fatty acids in OA. On the basis of recommended and typical ranges of the n -6: n -3 ratio, we hypothesized that in adults with knee pain, those with a high n -6: n -3 ratio would have greater pain/functional limitations, experimental pain sensitivity, and psychosocial distress compared with those with a low n -6: n -3 ratio. Materials and Methods: A cross-sectional investigation of clinical and experimental pain and physical and psychosocial functioning was completed in 167 adults ages 45 to 85 meeting knee OA screening criteria. Blood samples were collected and the plasma n -6: n -3 PUFA ratio determined. Quartile splits were computed and low (n=42) and high (n=41) ratio groups were compared. Results: The high ratio group reported greater pain and functional limitations, (all P s<0.04), mechanical temporal summation (hand and knee, P <0.05), and perceived stress ( P =0.008) but not depressive symptoms. Discussion: In adults with knee pain, a high n -6: n -3 ratio is associated with greater clinical pain/functional limitations, experimental pain sensitivity, and psychosocial distress compared with a low ratio group. Findings support consideration of the n -6: n -3 PUFA ratio and additional clinical endpoints in future research efforts. Abstract : Supplemental Digital Content is available in the text.